Konvergensi Media Batamtoday.com dan Batamnews.co.id Era Persaingan Teknologi Digital di Kota Batam - Taslimahudin Taslimahudin; Suyanto Suyanto; Yasir Yasir (UMSU, 2022)
AbstractThis paper is part of a study on convergence. Convergence is an online media effort to get a bigger readership, exist and struggle to improve services. This step is a strategy to face digital industry competition, especially in Batam City. Media Batamtoday.com and batamnews.co.id also carry out various convergence methods, such as the convergence of ownership, tactics, structure, coverage to presentation and journalistic convergence, newsgathering and content convergence which is one of the cores of this discussion. However, these two media converged according to the ability to invest, the need so as not to be trapped in mere technical problems. That is, the convergence carried out by the two media remains in the context of needs by looking at the existing competition patterns and opportunities. This type of research is descriptive qualitative. The purpose of this research is to find out how the media convergence. The results of this study are expected to be useful for knowledge for the community as well as for readers in general. In addition, as a first step for researchers to develop the knowledge and theory gained so far and is expected to increase interest in knowledge in the discipline of communication science. Furthermore, this study uses a qualitative descriptive method.Keywords: Convergence, online media, digital technology